1999
DOI: 10.1046/j.1440-1827.1999.00914.x
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of proliferative activity, DNA ploidy pattern and p53 products as diagnostic adjuncts in colorectal adenomas and intramucosal carcinomas

Abstract: Although numerous studies have assessed the biologic parameters of tumors, measurement of these parameters has had, to date, little impact on histologic diagnosis. Furthermore, analysis of a single parameter is insufficient to evaluate tumor malignant potential. In the present study, cell proliferation, DNA ploidy and p53 product were analyzed to objectify the tumor malignant potential in colorectal adenomas and intramucosal carcinomas. Sixty-one adenomas and 49 intramucosal carcinomas were studied using immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
12
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 22 publications
4
12
0
Order By: Relevance
“…In previous studies, p53 overexpression, which reflects mutations in p53, has been shown to be associated with aggressive clinical course in several types of cancer, including OPSCC, gastric cancer, and colorectal cancer (20,40,41). In the present study, p53 was frequently found to have a high PR (almost equivalent to overexpression) in HPV-negative OPSCC compared with that in HPV-positive OPSCC.…”
Section: Discussionsupporting
confidence: 58%
“…In previous studies, p53 overexpression, which reflects mutations in p53, has been shown to be associated with aggressive clinical course in several types of cancer, including OPSCC, gastric cancer, and colorectal cancer (20,40,41). In the present study, p53 was frequently found to have a high PR (almost equivalent to overexpression) in HPV-negative OPSCC compared with that in HPV-positive OPSCC.…”
Section: Discussionsupporting
confidence: 58%
“…Due to such heterogeneity, the cellular ploidy pattern seems to be dependent on the place where tumour material is extracted. Some authors claim that DNA analysis from one segment only is not sufficient (20,23,24). Rognum (15) observed that the more segments of the tumour that were examined, the more frequently aneuploid tumours were recognized.…”
Section: Discussionmentioning
confidence: 99%
“…Sugai (24) showed that among in 146 of 164 (89%) cases of colorectal carcinoma, at least one of six segments was aneuploid. He concluded that if a single segment is examined, aneuploid clones may be masked by assuming a CV that is too high, which results in false interpretation and qualifying such a clone to be diploid.…”
Section: Discussionmentioning
confidence: 99%
“…However, the possibility that polypoid cancer without any adenomatous region might derive from de novo cancer cannot be ruled out. In contrast, DNA aneuploidy is also closely associated with development of colorectal tumors 8–10 . In fact, DNA aneuploidy is thought to be an important risk factor for the increased malignant potential of colorectal adenomas 8–10 .…”
mentioning
confidence: 99%
“…In contrast, DNA aneuploidy is also closely associated with development of colorectal tumors 8–10 . In fact, DNA aneuploidy is thought to be an important risk factor for the increased malignant potential of colorectal adenomas 8–10 . Therefore, the association of DNA ploidy pattern with polypoid tumors is not yet fully understood.…”
mentioning
confidence: 99%